Selective Essential Oils from Spice or Culinary Herbs Have High Activity against Stationary Phase and Biofilm Borrelia burgdorferi - Feng, Jie; Zhang, Shuo; Shi, Wanliang; Zubcevik, Nevena; Miklossy, Judith; Zhang, Ying (Frontiers in Medicine, 2017)
Although the majority of patients with acute Lyme disease can be cured with the standard 2-4 week antibiotic treatment, about 10-20% of patients continue suffering from chronic symptoms described as post-treatment Lyme disease syndrome (PTLDS). While the cause for this is debated, one possibility is that persister bacteria are not killed by the current Lyme antibiotics and remain active in the system. It has been reported that essential oils have antimicrobial activities and some have been used by patients with persisting Lyme disease symptoms. However, the activity of essential oils against the causative agent Borrelia burgdorferi (B. burgdorferi) has not been well studied. Here, we evaluated the activity of 34 essential oils against B. burgdorferi stationary phase culture as a model for persister bacteria. We found that not all essential oils had activity against the B. burgdorferi stationary phase culture, with top 5 essential oils (oregano, cinnamon bark, clove bud, citronella, and wintergreen) at a low concentration of 0.25% showing high anti-persister activity that is more active than the known persister drug daptomycin. Interestingly, some highly active essential oils were found to have excellent anti-biofilm ability as shown by their ability to dissolve the aggregated biofilm-like structures. The top 3 hits, oregano, cinnamon bark and clove bud completely eradicated all viable cells without any regrowth in subculture in fresh medium, whereas but not citronella and wintergreen did not have this effect. Carvacrol was found to be the most active ingredient of oregano oil showing excellent activity against B. burgdorferi stationary phase cells, while other ingredients of oregano oil p-cymene and α-terpinene had no apparent activity. Future studies are needed to characterize and optimize the active essential oils in drug combination studies in vitro and in vivo and to address their safety and pharmacokinetic properties before they can be considered as a novel treatment of persistent Lyme disease.